A new species of Pactola Pascoe, 1876 (Coleoptera: Curculionidae: Eugnomini) from New Caledonia - Mazur, Miłosz A.; Jezuita, Anna (Zootaxa, 2015)
Pactola corporosa sp. n. is described from New Caledonia. Illustrations of body parts, terminalia of both sexes and distributional data of the new species are provided. The genus Pactola Pascoe, 1876 now contains thirteen species distributed in New Zealand, New Caledonia and Taevuni Island (Fiji Archipelago).